Influence of environmental parameters on microbiologically influenced corrosion subject to different bacteria strains - Muhammad Khairool Fahmy Mohd Ali,; Mardhiah Ismail,; Akrima Abu Bakar,; Norhazilan Md. Noor,; Nordin Yahaya,; Libriati Zardasti,; Abdul Rahman Md. Sam, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Microbiologically influenced corrosion (MIC) is capable on weakening the metal’s strength, eventually leads to pipeline leakage, environmental hazard and financial loss. Sulfate reducing bacteria (SRB) is the principal causative organism responsible for external corrosion on steel structures. To date, considerable works have been conducted in Malaysia on the mechanisms of SRB upon MIC on the marine environment instead of underground. Moreover, commercial bacteria strain represents local strain in terms of performance and behavior upon corrosion of steel structure is yet to be proven. Thus, this paper aims to investigate the influence of environmental parameters towards MIC in corroding pipeline. Two types of SRB strain were used designated as SRB ATCC 7757 (commercial) and SRB Sg. Ular (local strain) isolated from Malaysian soil. The behavior of both strains was critically compared by calculating the rate of corrosion upon carbon steel coupons in stipulated environmental parameters. Four influential parameters i.e. pH, temperature, salinity concentration and iron concentration were considered. Collected data presented and analyzed using graphical and statistical analysis, respectively. The results showed the difference of corrosivity between two SRB strains in terms of corrosion behavior upon the X-70 steel coupon. SRB Sg. Ular able to cause severe effects upon steel structure as compared to SRB ATCC 7757 due to its aggressiveness shown by the recorded metal loss data. Thus, future works related to MIC for local environment in particular, should not compromise with the type of SRB strains considered due to differences of performance of the microorganisms onto tested environment and materials.